Answer:
I think it's C.
Step-by-step explanation:
hope you get it right
Here is how you do it so they asked 120 kids and 46 of them hangs out
on Saturdays so you just do this 46/120=38%
Answer:
x=-6 y=-1
Step-by-step explanation:
// Solve equation [2] for the variable y
[2] y = -x - 7
// Plug this in for variable y in equation [1]
[1] 3x - 2•(-x -7) = -16
[1] 5x = -30
// Solve equation [1] for the variable x
[1] 5x = - 30
[1] x = - 6
// By now we know this much :
x = -6
y = -x-7
// Use the x value to solve for y
y = -(-6)-7 = -1
Solution :
{x,y} = {-6,-1}
Answer:
The answer is below
Step-by-step explanation:
The question is not complete. But I would show you how to solve the problem.
Two events A and B are said to be independent if the occurrence of event A does not affect the occurrence of event B and vice versa. P(A and B) = P(A) * P(B).
Two events A and B are said to be mutually exclusive if event A and event B cannot occur at the same time. P(A and B) = 0.
Two events A and B are said to be complementary when event A occurs if and only if event B does not occur and vice versa.
Answer:
![-2x^{2} -7x-6](https://tex.z-dn.net/?f=-2x%5E%7B2%7D%20-7x-6)
Step-by-step explanation:
(2x + 3) (-x - 2)
distribute first term, to the second term:
2x(-x) + 2x(-2) + 3(-x) + 3(-2)
multiply:
+ (-4x) + (-3x) + (-6)
![-2x^{2} -4x-3x-6](https://tex.z-dn.net/?f=-2x%5E%7B2%7D%20-4x-3x-6)
combine the like terms:
- 4x - 3x - 6
-7x
- 7x - 6
final answer :
- 7x - 6
hope this helped !!
mark me brainliest :D